Facebook Addition and Brand Tracking: Case Study Eastern Mediterranean University - Yeganli, Hanieh (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
The study ‘Facebook Addiction and Brand Tracking’ was conducted to investigate and assess the addiction to Facebook, and its role in remembering and following brands. The focus of this study is to analyze the addiction of Facebook among Eastern Mediterranean University students, and how these students build a relationship with their favorite brands. With the use of quantitative research method, the survey method was established as the main tool for the research. A sample size of 400 respondents who represented 10% of the population was issued questionnaire consisting of 30 questions. Of the 400 questionnaires, none was left behind, they were all returned. The questionnaire was divided into two, which consisted 200 English questionnaires and 200 Turkish questionnaires. In respect to respondents sex, T-Test was conducted to assess the significant differences between the mean of respondents. The result of the study indicates that all 400 respondents use social media, and 38.5% of the sample particularly make use of Facebook compared to other social media. The main reasons student use Facebook is for checking news online, exchanging messages and sharing photos and videos. In the results, 45% of students turn on the internet for information on their favorite brands. Facebook advertising is very good and effective affirms 48.5% of the study. Keywords: Social Media, Facebook, Addiction, Brand, Advertisement.

ÖZ: ‘Facebook Bağımlılığı ve Marka Takibi’ çalışması, Facebook bağımlılığı ve bu bağımlılığın markaların hatırlanma ve takip edilmeleri üzerindeki etkisini incelemek ve belirlemek için gerçekleştirilmiştir. Bu çalışmanın odak noktası, Doğu Akdeniz Üniversitesi öğrencilerinin Facebook bağımlılık düzeylerini araştırmak ve bu öğrencilerin favori markalarıyla kurdukları ilişkileri incelemektir. Nicel araştırma metodunun kullanımıyla, anket methodu bu araştırma için ana araç olarak kullanılmıştır. Popülasyonun 10%’unu temsil eden 400 katılımcıya 30 sorudan oluşan anket soruları soruldu. Dağıtılan 400 anketten tamamı cevaplandı ve geri dönüşü sağlandı. Anket, 200 adet İngilizce ve 200 adet Türkçe olmak üzere ikiye bölündü. Cinsiyete bağlı farklılıkları tespit etmek için, katılımcıların ortalama cevapları üzerinden T-Test’i uygulandı. Çalışma, tüm katılımcıların sosyal medya kullandığını ve 38.5%’inin diğer sosyal medya araçlarına kıyasla özellikle Facebook’u kullandığını göstermiştir. Öğrenciler Facebook’u çoğunlukla haberleri takip etmek, mesajlaşmak ve fotoğraf/video paylaşmak için kullanıyor. Çalışma, öğrencilerin 45%’inin interneti favori markaları hakkında bilgiler edinmek için de kullandığını gösterdi. Çalışmanın 48.5%’i Facebook reklamcılığının çok iyi ve etkili olduğunu onayladı. Anahtar kelimeler: Sosyal Medya, Facebook, Bağımlılık, Marka, Reklam.
Master of Arts in Communication and Media Studies. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Communication, Dept. of Communication and Media Studies, 2016. Supervisor: Assoc. Prof. Dr. Agah Gümüş.
Keywords: Communication and Media Studies; Internet marketing-Social Networking Sites-Facebook-Adevertisements; Internet advertising-Online social networks-Facebook; Social media-Marketing-Internet marketing-Social marketing; Social Media; Facebook; Addiction; Brand; Advertisement